ANALISIS PENGARUH KETIDAKHOMOGENAN FANTOM TERHADAP DISTRIBUSI DOSIS ELEKTRON MENGGUNAKAN SIMULASI MONTE CARLO - Gaspersz, Daniel Gibbor; Manik, Josua Timotius (Program Studi Pendidikan Fisika FKIP Universitas Muslim Maros, 2024)
The usage of homogeneous phantom in the calibration of LINAC is the standard in radiotherapy. However, a homogeneous phantom cannot accurately represent the complexity of the human body. This study was conducted to perform a Monte Carlo simulation of electron beam irradiation on an inhomogeneous phantom and then compare the resulting dose distribution values, in the form of PDD, with the PDD values obtained from a homogeneous phantom. Irradiation was performed with a 6.6 MeV electron beam on an inhomogeneous phantom resembling the human body. It was discovered that there is a significant difference between the R100 and R50 values of the inhomogeneous phantom in comparison to the homogeneous water phantom. The R100 value of the inhomogeneous value differs by 53.33% compared to the homogeneous phantom, while the R50 value differs by 41.07%. This indicates the influence of electron beam interaction with the inhomogeneous phantom on the resulting dose distribution. In the PDD curve, it is observed that the electron beam passing through the inhomogeneous medium experiences a greater loss of kinetic energy compared to the homogeneous medium. It was found that there’ a significant difference between the PDD values generated in the inhomogeneous phantom compared to the homogeneous phantom.